Business as usual : the economic crisis and the failure of capitalism - Mattick, Paul, 1944- (Reaktion Books, 2011)
The recent global economic downturn has affected nearly everyone in every corner of the globe. Its vast reach and lingering effects have made it difficult to pinpoint its exact cause, and while some economists point to the risks inherent in the modern financial system, others blame long-term imbalances in the world economy. Into this debate steps Paul Mattick, who, in Business as Usual, explains the global economic downturn in relation to the development of the world economy since World War II, but also as a fundamental example of the cycle of crisis and recovery that has characterized capital.